E-business As An Entry Point For Strengthening Health Services Case Study - Aziez, Yasmine; Ben Bordi, Hanan (جامعة الوادي University of Eloued, 2024)
The study aimed to highlight contemporary electronic and digital works and their application in the Hospital Ophthalmology Foundation Friendship of Algeria-Cuba in the Valley, by addressing both the idea of electronic business and health services and exploring the term "e-health" and its contribution to improving and strengthening the work of the institution in question. The study concluded that the health enterprise was significantly affected by advances in ICT and e-business through its support with advanced tools and devices supported by AI technologies, which significantly improved and enhanced the institution's health services.
E-business as an entry point for strengthening health services Case study: Foundation Ophthalmic Hospital Friendship of Algeria Cub in the eloued
Keywords: E-Business; Health Services; E-Health Services